Managerial Performance of a Female-Owned and Home-Based Firm - Oluwasheyi S. Oladipo; Katarzyna Platt; Hyoung Suk Shim (Institute of Labor Economics (IZA), 2020)
Female entrepreneurship has been regarded as inferior to its male equivalent in terms of performance. Literature on gender differences in entrepreneurship focus mostly on showing the differences, but not much literature discusses where the differences come from, and how to mitigate them. This paper empirically examines the joint effect of female ownership and being home-based on owners' managerial performance. We estimate the average treatment effect of female-owned and homebased firms on return on assets (ROA) using the 2007 Survey of Business Owners (SBO) micro data. From the main estimation result, the marginal effects of female ownership and home-based business are both negative. The estimated ROA gains of female ownership and home-based business are about -37.20% and -67.17%, respectively. In contrast, we find that the joint effect of female ownership and home-based business is about 39.53% ROA gain. Our finding suggests that female-owned firms can outperform under the appropriate supporting conditions, such as if they are able to remove travel time and costs by establishing their businesses at home.
Keywords: L25; L26; J16; 330; firm performance; female owners